The Impact Of The Covid-19 Pandemic On Expenditure Household Of Dusung Farmers: A Case Study In Rutong Country, South Leitimur District, Ambon City - Helma F Maspaitella; Wardis Girsang; August. E. Pattiselanno (International Journal of Economics, Business and Innovation Research, 2023)
The Covid-19 pandemic has disrupted various development sectors, especially health, education and transportation in villages and cities. The purpose of this study is to look at the impact of the Covid-19 pandemic on household expenditures in Rutong Country. The research method used surveys and interviews with 40 heads of households. The results showed that food expenditure was greater than non-food, namely food expenditure was 59% higher than non-food 41%, indicating that the standard of living of most households was at the poverty line. The Covid-19 pandemic has had an impact on household food expenditure. This has implications for the importance of government attention in strengthening household food security based on local resources.